(untitled) (Herald of Journalism, 2021)
In 2019, the Kazakhstani government attempted to embed the installation of a national security certificate within the country. The introduction of such a certificate was explained by the need to strengthen the cyber protection of citizens, state bodies, private companies from activities of Internet fraudsters and other types of cyber threats. However, citizens alongside local and international experts did not entirely welcome and accept this decision by voicing their dissent towards it. Criticism towards the installment of national security certificate ranged from infringements concerning personal data rights of citizens and companies towards an act of state apparatus espionage on sensitive private information. The thematic focus of the paper concerns the problem of mass communication and realm of media rights. Structurally, the paper first describes how the national security certificate was introduced and has originated in Kazakhstan. Then the paper analysis the various reasons and arguments in favor or against the introduction of a national security certificate. Here, viewpoints from different stakeholders were considered, such as by state ministries, Kcell and Activ mobile operators, ordinary citizens or local experts like Dossym Satpayev. Lastly, a thorough analysis of present and future outlooks on the development of national security certificate in Kazakhstan is discussed. A discourse analysis approach is applied as a research method with secondary sources of information used. The goal of this concise but informative article is to highlight both the development and the inter-relationship between the society and state what concerns national policies within the cyber realm. The significance of this paper is that it should help scholars in identifying new domestic issues studying in the field of journalism or public policy. In conclusion, the results and discussions of this paper showed us the practical and theoretical importance of how a national policy and its security certificate project generated both public dissatisfaction and new social movements concerning cyberspace aspects, but also a new testing ground for pilot projects in testing people’s readiness for accepting new cyberspace regulations. Keywords: national security certificate; Kazakhstan; Internet blocking; mobile operators; human rights.